Exploration of Information Needs for 3rd Trimester Pregnant Women with Severe Preeclampsia at Banyumas Hospital - Susbika Fitriyanti; Happy Dwi Aprilina (Proceedings Series on Health & Medical Sciences, 2024)
Background: Preeclampsia is a munciton characterized by high blood pressure during pregnancy, with symploms such as body weling, especially in the face and hands, a sudden increase in blood pressure, and high protein levels in the une, several rise factors can increase the Molhood of developing preeclampsia/eclampsia at an individual level including a history of chronic hypertension, obesity, and severe anemia. Liteacy of the pregnant women can influence their behavior toward preventing severe preeclampsis Providing information is expected to enhance knowledge and reduce anxiety among pregnant woment. Methods: This study aims to explore the information needs of tri-mester pregnant women with severe preeclampsia at Banyumas Hospital. This qualitative exploratory study used interview methods. The subjects were 10 pregnant women with severe preeclampsia at Banyumas Hospital, selected through purposive sampling. The data analysis involved qualitative techniques, including data reduction prosentation, and conclusion. Results: The research results show that most informants (8 women) are adults (aged 26-45). Their educational level is primarily high school (SMA), with 8 individuals Moat are housewives (fi individuals), and 9 have more than one child or are mutparous. Conclutions: Overall, all informants require information to support their pregnancy up to the delivery process, such as education on understanding severe preeclampsia, managing atuty and fear of preeclampsia risks, and being aware of matomal health.